HEALTH RELATED QUALITY OF LIFE IN ADOLESCENCE WITH VARIED LEVEL OF DIGITAL SCREEN USE: A QUANTITATIVE ANALYSIS - 1. Ms Ashwini S Shetty , 2. Dr Rajeshwari N Kenchappanavar (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
When an individual is no longer a child but not yet an adult is described as the period of adolescence. This phase of development involves polymorphic affects in one’s life. Being a sensitive period, they do undergo lot of physical and psychological changes. Digital screen use is an activity found to be more generously involved by the people in the modern era. It aligns with both positive and negative outcomes in the people life and recognised as a good scope of research in different age groups. Health Related Quality of Life can be viewed as a psychological construct which describes the physical, mental, social, psychological and functional aspects of well-being and function. This study intends to assess the impact of digital screen use on the health-related quality of life in early, middle and late phase of adolescence. The sample size is 120 adolescents of age 10-19 years residing in Dakshina Kannada district. The study adopts systematic random sampling method and cross-sectional research design for data collection. The demographic details like gender and domicile was collected using the semi-structured interview. The Questionnaire for screen time of adolescents (QueST) and Kidscreen-27 scale was used for data collection. The result was analysed using ANOVA.